Microstrip patch antenna design for brain cancer detection - Ali N,; Saiti .A,; Elkharam .R. (Aljameai, 2023)
Abstract:     Brain cancer is an abnormal proliferation of brain cells, which can be classified as benign or malignant. In this study, a micro strip antenna was developed that operates at microwave frequencies in the ISM band. It was implemented on a simplified model of both normal and abnormal brain tissue, and it was used to compare the return loss, gain, and directivity, as well as the electric field, magnetic field, and specific absorption rate, in order to detect the presence of a stage II tumor. CST microwave studio was used for all simulations and results.المستخلص:في هذه الدراسة، تم تطوير هوائي شريطي صغير يعمل على ترددات الميكروويف في نطاق الترددي الطب تم تنفيذه على نموذج  لرأس مبسط لكل من أنسجة المخ الطبيعية وغير الطبيعية ، وتم استخدامه لمقارنة خسارة العودة ، والكسب ، والاتجاهية ، وكذلك المجال الكهربائي ، والمجال المغناطيسي ، ومعدل الامتصاص النوعي، نظرا لاختلاف الخصائص العازلة للأنسجة السليمة وغير الطبيعية عند ترددات الميكروويف يمكن استخدام هذا الاختلاف لتحديد ما إذا كان النسيج الورمي موجودًا أم لا. تم استخدام برنامح محكاه  للتصميم  الهوائي والنموذج الراس واخرج النتائج ومقارنتها.